Histopathological and Biochemical effects of aqueous leaf extract of Cadaba farinosa on the liver of adult Wistar Rats - Gamde, Solomon M.; Kabiru, Hauwa; Abdulazziz, Aisha; Abubakar, Khadijah A.; Musa, Abdurahman A.; Perede, Anthony (International Journal of Research in Medical Sciences, 2019)
Background: Plants are important source of chemical substances with therapeutic effects. Although, the promising potentials for good number of medicinal plants are being established, there exists in developing countries where people resort to herbal plants without proper awareness of the associated risks particularly in event of excessive or chronic use. Hence, the need to evaluate the histological and biochemical effects of aqueous leaf extract of Cadaba farinosa used traditionally for treatments of gastrointestinal parasites, cancer and diabetes in North-Eastern Nigeria. To evaluate the histological and biochemical effects of aqueous leaf extract of Cadaba farinosa on liver of adult Wistar rats. Methods: Twelve adult Wistar rats of both sexes were used and divided into four groups of three rats each. Group 1 served as control. Aqueous leaf extract were orally administered for 28 days at doses of 100, 200 and 300mg/kg respectively. Biochemical and histological analysis were performed. Results: This study showed significantly elevated levels of aspartate transaminase, alkaline phosphatase and alanine transaminase in animals treated with Cadaba farinosa (especially the highest dose 300mg/kg) compared to negative control. Elevated liver enzymes were corroborated by histopathological changes of liver exhibiting ballooning degenerations and steatohepatitis. Conclusions: Cadaba farinosa causes hepatic injury. Hence, further work needs to be done to ascertain whether reducing the dose of Cadaba farinosa would ameliorate this effect. Authors speculate that injury to multiple organelles including fat droplets and endoplasmic reticulum contribute to this characteristic finding.